COMPARISON OF THE RADIATION SITUATION IN THE AGRICULTURAL AND OIL REGIONS OF THE ATYRAU REGION - Yessenamanova Mansiya,; Salamatova Zhazira,; Sangadzhieva Ludmila,; Yessenamanova Zhanar,; Tlepbergenova Anar, (Academic Journal of Physical and Chemical Sciences, 2021)
The article is devoted to the comparison of radiation levels in the Issatay and Makhambet districts of the Atyrau region. Atyrau region belongs to the regions of the oil-producing industry, which in turn can lead to environmental pollution, including radiation. Therefore, a radiation analysis was carried out to measure the exposure dose on the territory of the Isatai region, in which the oil-producing industry is developed, and for comparative analysis, the same measurements were carried out in the Makhambet region, where there is no industrial activity and the region belongs to an agricultural region. The studies carried out show that, according to the average values of the exposure dose in both regions, it is in close values, which range from 9 to more than 14 mR/h in the industrial region (Issatay region) and from 10 to 11 mR/h in the agricultural region (Makhambet region). In the Issatay district, according to the average values, there is a slight increased content. The data on the exposure dose rate at the entrance to the village and in the center of the village show that in the Makhambet district, the exposure dose data is higher in the center of the village than at the entrance to the village, while in the Isatai district the indicators at the entrance to the villages are, on the contrary, higher. In the Issatay region, within the villages, the data are similar to the Makhambet region, and outside the settlements, there is a slight increase associated with the additional load from oil pollution. The data on the level of measurement height show that at the level of the earth's surface and at the level of 50 cm, the values of the exposure dose are close in the values of the two regions, while there is a difference at the level of 1 m. In the Issatay region, the exposure dose is higher than in the Makhambet region, this may be due to the relatively greater accumulation of gaseous radioisotopes that accumulate as a result of evaporation from oil fields. The background radiation in both regions does not exceed the maximum permissible dose and is not hazardous to health.